Clinical significance of P16-positive status and high index of proliferative activity in patients with oropharyngeal squamous cell carcinoma - A. I. Stukan; V. A. Porkhanov; V. N. Bodnya (Сибирский онкологический журнал)
Introduction. In accordance with uICC and AJCC 8th edition TNM classifications, there is a strong evidence for division of oropharyngeal squamous cell carcinoma (OPSCC) into 2 molecular subtypes by HPV-status with distinct prognosis depending on biological differences. Such a division leads to differences in staging OPSCC and in future it will lead to implementation of preventive measures and new therapeutic strategies against HPV-positive cancer.Aim of the study: to assess the clinical and prognostic significance of the combination of P16, a surrogate marker for HPV-positivity, and high proliferative activity in patients with oropharyngeal carcinoma.Material and Methods. Immunohistochemical (ICH) analysis with monoclonal antibodies specific for P16 and Ki67 proteins was used to detect expression patterns in the formalin-fixed, paraffin-embedded tumor samples obtained from 104 patients with squamous cell carcinoma of the tongue and oropharynx, treated at Oncological Dispencery № 1 in Krasnodar from 2011 to 2016. HPV-positive status was determined if more than 70 % of tumor cells had moderate or strong nuclear and cytoplasmic P16-staining. High index of proliferative activity (PA) was detected if more than 50 % tumor cells expressed Ki67 nuclear antigen.Results. P16-positivie status was associated with tonsillar cancer (р=0.002), female gender (р=0.015), age <60 years (р<0.001), non - keratinizing morphology (р=0.022), and high index of PA (p=0.01).The combination of P16>70 % with high PA demonstrated correlation with tonsillar cancer (р<0.001), female gander (р=0.015), age under 60 years (р<0.001) and non - keratinizing morphology (р=0.012). HPV-positive patients and patients with a combination of P16>70 % and high index of PA at N1-2 had an overall survival benefit (p=0.021).Conclusion. The correlation between IHC-complex for P16>70 %/Ki67>50 % and clinicopathologicl parameters and overall survival confirms the biological features of HPV-associated cancer. The evaluation of this IHC-complex can increase the diagnostic accuracy of IHC-analysis of HPV-status and predict the prognosis of patients with OPSCC.